SISTEM MONITORING KELEMBABABAN TANAH TUMBUHAN BONSAI BOUGENVILL SINGAPORE BERBASIS IOT MENGGUNAKAN ESP 32 S3 - Sri Rejeki; Asep Suryadi (PSRE UNIMUS, 2025)
This research successfully developed and implemented an integrated soil moisture monitoring system based on the Internet of Things (IoT), utilizing the ESP32-S3 microcontroller. The system is specifically designed for the cultivation of Bougainvillea Singapore bonsai, aligning with the principles of smart agriculture. The primary function is to monitor soil moisture conditions in real-time and automatically classify the sensor data. Classification is achieved through an If-Else logical method, defining three distinct conditions that also control the irrigation actuator: dry (0%–25%), which triggers the pump ON; moist (26%–69%), which keeps the pump OFF; and wet (70%–100%), which also maintains the pump in the OFF state. The system demonstrated good accuracy in identifying soil moisture status. This success not only validates the system's design but also confirms the significant application potential of this technology for further development as a precise and automated solution supporting optimization within sensor-based smart farming systems.